1992
DOI: 10.2134/jpa1992.0340
|View full text |Cite
|
Sign up to set email alerts
|

Forage Legume-Small Grain Intercrops: Nitrogen Production and Response of Subsequent Corn

Abstract: Frost‐seeding a legume into an established stand of winter wheat (Triticum aestivum L.) or interseeding a legume into a small grain at planting has potential to provide the benefits of a legume green manure while still allowing for the harvest of a revenue‐producing crop. Field studies were conducted at three Michigan locations to quantify N accumulation by alfalfa (Medicago sativa L.) and red clover (Trifolium pratense L.) frost‐seeded into winter wheat or interseeded with oat (A vena sativa L.) and to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
75
1
3

Year Published

1996
1996
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(90 citation statements)
references
References 15 publications
11
75
1
3
Order By: Relevance
“…It has been suggested that for an FRV to be valid, the yield of the crop following the legume must be significantly higher than that following a non-legume control when no N fertilizer is used in either system (Hesterman et al 1992). Based on this, FRV of the legumes were non-estimable in our study because winter canola yields following legumes and the non-legume control at the 0 N level were not significantly different in either year.…”
Section: Nitrogen Fertilizer Replacement Valuesmentioning
confidence: 56%
See 3 more Smart Citations
“…It has been suggested that for an FRV to be valid, the yield of the crop following the legume must be significantly higher than that following a non-legume control when no N fertilizer is used in either system (Hesterman et al 1992). Based on this, FRV of the legumes were non-estimable in our study because winter canola yields following legumes and the non-legume control at the 0 N level were not significantly different in either year.…”
Section: Nitrogen Fertilizer Replacement Valuesmentioning
confidence: 56%
“…Fertilizer replacement values have generally been reported in crops planted the following year after legumes, e.g., in corn seeded in the spring following a legume grown in the previous summer or fall (Hesterman et al 1992). Jeranyama et al (1995) estimated FRV of annual medics as 40 kg N ha -1 in the corn planted the following year.…”
Section: Nitrogen Fertilizer Replacement Valuesmentioning
confidence: 99%
See 2 more Smart Citations
“…New local techniques used for cover crop establishment include interseeding into young standing corn using a specialized interseeder that also side-dresses fertilizer and applies herbicide, or interseeding in chest-high corn with a highboy applicator that drops cover crop seeds between standing rows of corn. Frost seeding red clover (Trifolium pratense L.) into standing wheat or barley in February or March (Hesterman et al 1992) is a method used to establish a leguminous cover crop that will occupy the field after small grain harvest. Relatively new cover crops such as forage radish (Raphanus sativus L.), annual ryegrass (Lolium multiflorum Lam.…”
mentioning
confidence: 99%